Answer:
a) 
b) The inverse function is a reflection of the original function across the line
y = x. For example, if the function f applied to an input x gives a result of y, then applying its inverse function g to y gives the result x. So you would use it to find the x-value at a y just like you use the original to find the y value at an x.
Step-by-step explanation:
To do an inverse of a function you first switch the independent variable (d) and the dependent variable (c).
d = 0.45c + 5.50
Then you solve for c
d - 5.50 = 0.45 c
c = (d-5.50)/0.45
It is okay to take the inverse of both side given that you remember to exclude the value that make the denominator zero which is in this case r=-1
Answer:
x•(2xy-3z)
Step-by-step explanation:
2x²y -3xz== x(2xy-3z)
That's answer exactly is -5